POLIGAMI DALAM PANDANGAN MUHAMMAD SYAHRUR: Pembacaan Ulang Terhadap Makna dan Ketentuan Poligami - Khozainul Ulum (Al Hikmah: Jurnal Studi Keislaman, 2015)
In Islam, polygamy is a form of justified marriage. Many Muslimscholars or mufassir have allowed a man to perform polygamous marriages.However, their thinking about the permissibility of polygamy is sued andcriticized by a group of contemporary Islamic thinkers who tend not to justify itwith the logical reasons based on their understanding of the Qur'an. One of thecontemporary Islamic thinkers who also takes into account the issue of polygamyis Muhammad Shahrur. However, his points of view about polygamy aredifferent from most other contemporary thinkers. Although the Shahrur'scharacteristics of thought could be considered post-traditionalistic, his points ofview about it are far different from the ones of most contemporary Muslimintellectuals in which they tend to forbid it with the main reason, namely theimpossibility of a man to do justice between his wives. At this point, knowingthe Shahrur's thought related to the issue of polygamy is very interesting.